Analisis Pengaruh Inflasi dan Fluktuasi Harga Emas Terhadap Realisasi Zakat Maal di Indonesia - Dodi Sunanto; Finita Rahmadhani; Sri Rahayu; Syaeful Bakhri; Abdul Aziz (MASILE, 2026)
Abstract This study analyzes the simultaneous and partial effects of inflation as well as global gold price fluctuations on the realization of zakat maal revenue in Indonesia. Using monthly data from 2023 to 2025 and the Vector Error Correction Model (VECM), this study reveals the dynamics of short-term and long-term relationships between macroeconomic variables and the performance of national zakat maal collection. The Johansen cointegration test successfully confirmed the existence of two cointegration vectors, indicating a strong long-term equilibrium relationship among the variables under study. In the short term, changes in inflation have a positive and significant effect on zakat maal collection, where a 1% increase in inflation increases zakat maal collection by Rp9.93 billion. Additionally, zakat maal collection from the previous period also significantly influences gold price fluctuations, with a Rp1 billion increase in zakat maal collection causing a 0.00262% decrease in gold price fluctuations by 0.00262%. This finding indicates that the surge in the value of muzaki’s assets due to gold price fluctuations also drives an increase in zakat maal obligations denominated in rupiah. Overall, this study confirms that inflation and global gold price fluctuations are important macroeconomic factors that influence the realization of zakat maal revenue. The results of this study provide policy implications for Baznas and economic regulators to integrate macroeconomic outlook analysis into strategic planning for zakat management, as well as to formulate risk mitigation strategies to maintain the stability of zakat revenue amid global economic uncertainty. Keywords: Gold Price Fluctuations; Inflation; Makroeconomics; Realization of Zakat Maal.